Analisa Kebijakan Pemerintah di Kota Batam Terkait Ancaman Pengangguran Pasca Inflasi antara Tahun 2018 - 2020 - Raihan, Raihan; Sahat Juliwan Tarihoran; Kevin Jonay Lie; Tesalonika Sembiring; Jhohari, Jhohari (Populer: Jurnal Penelitian Mahasiswa, 2022)
Inflation is closely related to unemployment and the economic performance of a country. The relationship between the inflation rate and unemployment affects decisions to be taken in financial policy. The purpose of this article is to analyze government policies in Batam City regarding the threat of unemployment in inflation in 2018-2020. The method we use is library research. From the results of our analysis, we find that the highest unemployment rate is in 2020 at 11.79% . And the movement of inflation has increased and decreased. We also analyze the policies that can be taken by the Batam city government in overcoming this problem.